Emotional responses of college students to filtered fluorescent lighting in a classroom (v3) - Hon K. Yuen; Anna L. Wood; Jane E. Krentel; Robert A. Oster; Anthony D. Cunningham; Gavin R. Jenkins (Health Psychology Research)
# Background